2010
DOI: 10.1038/ejcn.2009.145
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and socioeconomic position

Abstract: Background/Objectives: To test a socioeconomic hypothesis on three dietary patterns and to describe the relation between three commonly used methods to determine dietary patterns, namely Healthy Eating Index, Mediterranean Diet Score and principal component analysis. Subjects/Methods: Cross-sectional design in 1852 military men. Using mailed questionnaires, the food consumption frequency was recorded. Results: The correlation coefficients between the three dietary patterns varied between 0.43 and 0.62. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
95
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 38 publications
18
95
2
7
Order By: Relevance
“…In the present study, we found a small but significant indication that children whose parents had lower educational and occupational levels consumed a cheaper and less-healthy diet. The relationship between dietary quality and SEP is in line with several other studies based on both Swedish and international data (2)(3)(4)(5)(6)(7)49) . There are, however, few studies examining the relationship between actual dietary costs and SEP. Waterlander et al found no difference in actual food costs among income levels in adults; however, they suggested that the lack of significance could be due to the small number of participants in the lowincome groups (21) .…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we found a small but significant indication that children whose parents had lower educational and occupational levels consumed a cheaper and less-healthy diet. The relationship between dietary quality and SEP is in line with several other studies based on both Swedish and international data (2)(3)(4)(5)(6)(7)49) . There are, however, few studies examining the relationship between actual dietary costs and SEP. Waterlander et al found no difference in actual food costs among income levels in adults; however, they suggested that the lack of significance could be due to the small number of participants in the lowincome groups (21) .…”
Section: Discussionsupporting
confidence: 90%
“…Why a lower socioeconomic position is associated with higher consumption of sugar-sweetened beverage is not clear, but the low cost and aggressive marketing in low-income areas could be an explanation. In previous research, low socioeconomic position in this population has been associated with a clustering of unhealthy lifestyles, such as smoking, unhealthy dietary patterns and obesity (Mullie et al, 2010b). Drinking daily sugar-sweetened beverages can be seen as an unhealthy habit due to the high-energy content of the beverages and the low nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…219 Socioeconomic gradients exist for multiple health behaviors over the life course, and the combination of several unhealthy behaviors adds up to explain a large part of the socioeconomic health gap. Smoking, poor diet, inactivity, obesity, and medication nonadherence tend to be more prevalent among individuals of low SEP. [220][221][222][223][224][225] Furthermore, SEP in childhood helps account for unhealthy behaviors and health risk in the adult years. For example, a British cohort study that followed up subjects from birth to 66 years of age found that both childhood and adult SEP (ie, father's occupational class and mother's education) accounted for a significant portion of health inequalities in mortality risk by shaping exposure to smoking and other risk behaviors.…”
Section: Behavioral Mechanismsmentioning
confidence: 99%